Inclusion of curcumin in β-cyclodextrins as potential drug delivery system: preparation, characterization and its preliminary cytotoxicity approaches - Muhammad Hasnor Ja'far,; Nik Nur Syazni Nik Mohamed Kamal,; Boon, Yih Hui; Muhammad Fahmi Kamaruzzaman,; Nur Nadhirah Mohamad Zain,; Noorfatimah Yahaya,; Muggundha Raoov, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The development and application of organic based drug carrier in drug delivery system (DDSs) with greater efficacy and fewer side effects remains a significant challenge in modern scientific and medical research. The aim of current study was to evaluate the ability of β-cyclodextrin (β-CD) as drug delivery carrier to encapsulate Curcumin (CUR), a promising chemotherapeutic that exhibits low aqueous solubility and poor bioavailability forming inclusion complex by kneading method to enhance its delivery to cancer cells. Different methods and analysis such as Fourier Transform Infrared (FTIR) spectrometer, 1H Nuclear Magnetic Resonance (1H NMR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and Thermo-gravimetric Analysis (TGA) were employed to approve the successful formation of the inclusion complex where the aromatic ring of CUR has been encapsulated by the hydrophobic cavity of β-CD. UV absorption indicated that β-CD complex with CUR with an apparent formation constant of 1.09 × 10-8mol-1dm-3. Based on the data obtained by methylthiazole tetrazolium (MTT), β-CD showed that not only did it enhanced Curcumin delivery, but it also improved and promoted the anti-proliferative effect of CUR during the complexation rather than CUR alone on the MCF-7 human breast cancer cells at 24 h incubation period with IC50 lower than that of Curcumin alone. The toxicities of the β-CD-CUR towards MCF-7 cells were also compared to the free tamoxifen, Curcumin and β-CD. This study provides a preliminary toxicity evaluation based on β-CD-CUR inclusion complex as potential delivery system towards the selected cancer cells.